Puerperal ileal perforation secondary to endometriosis: Case report and literature review - Judit Albareda; Manuel Victor Albi; Grevelyn Sosa; Ana Cano; Manuel Emilio Macello; Beatriz Albi Martin (Elsevier, 2016)
Objective: Bowel endometriosis is an uncommon disease that can cause serious complications and may require immediate medical attention. We wish to remind about bowel perforation caused by endometriosis, its diagnostic difficulty, and the need or urgent management in late pregnancy and puerperium. Case Report: We present a 38-year-old woman, which presented with bowel perforation requiring urgent surgery. A pathological exam disclosed deep ileal infiltrative endometriosis. Conclusion: Even though bowel endometriosis is a rare complication, it should be considered in the differential diagnosis of severe abdominal pain in late pregnancy or puerperium. A multidisciplinary management of these patients is needed.